THE COST OF TERRITORIALITY: JUS COGENS CLAIMS AGAINST CORPORATIONS - Doyle, Ursula Tracy (Case Western Reserve journal of international law, 2018)
In Jesner v. Arab Bank PLC the US Supreme Court held that "foreign corporations may not be defendants in suits brought under the [Alien Tort Statute ("ATS")]," a US federal statute. The ATS states that "[t]he district courts shall have original jurisdiction of any civil action by an alien for a tort only, committed in violation of the law of nations or a treaty of the US."